Pembuatan Website Marketplace Untuk Pariwisata di Pulau Timor - Viky George Lettu Radja Pono; Djoni Haryadi Setiabudi; Justinus Andjarwirawan (Jurnal Infra, 2015)
Website is one of the media information that can be accessed by people from different areas with internet access. Therefore develope a website that contains information about the tourist attractions that can be visited, and a place to meet travel agents with the tourists. So they can make buying and selling tour packages without having to meet face to face.The tourists can find comprehensive information about travel agent and tour packages are offered, that can help the tourists to plan a better vacation. Making this website using the programming language PHP, javascript and MySQL databaseThe website is expected to be a means of information and the transaction of  buying and selling tour packages. And can assist travel agents to conduct the promotion of existing attractions. So as to more easily access information will increase the number of tourists who will come to the island of Timor.